Implementation of a Higher Order Thinking Skills (HOTS)-Based Chemistry Module with a Science, Technology, Engineering, and Mathematics (STEM) Approach on Thermochemistry Material - Nasution, Haqqi Annazili; Darmana, Ayi; Daulay, Rabiah Afifah; Kurniawan, Ekin Dwi Arif (Jurnal Riset Ilmu Pendidikan, 2025)
Chemistry learning requires innovative strategies to enhance students' understanding, particularly in thermochemistry, which is often considered challenging. This study aims to evaluate the effectiveness of implementing a Higher Order Thinking Skills (HOTS) and Science, Technology, Engineering, and Mathematics (STEM)-based chemistry module in improving students' learning outcomes. A quasi-experimental method with a pretest-posttest design was employed in this research. The subjects were students learning thermochemistry using the Higher Order Thinking Skills (HOTS) and Science, Technology, Engineering, and Mathematics (STEM)-based chemistry module. Data were collected through pretest and posttest assessments and analyzed using n-gain calculations to measure learning improvement. The results showed that the average n-gain obtained was 0.372, classified as a moderate category. These findings indicate that the chemistry module effectively enhances students' understanding, although the improvement is not yet optimal. Several factors, such as limited instructional time and students' readiness in comprehending the module, may have influenced the results. Therefore, further development is needed to optimize the module's effectiveness, such as integrating discussion-based and hands-on experimental learning methods.